Formação de educadores de ciências da EJA: possibilidades e desafios da articulação Freire-CTS-Andragogia - Ribeiro, Renata Deli da Rosa (2022)
This paper sought to investigate the possibilities and challenges that a training process based on the Freire-CTS-Andragogy principles presents to the knowledge and practices of educators in the area of Natural Sciences who work in YAE. Through this path, it is initially presented a look at the productions that contemplate such assumptions in their contents from the analysis carried out in the minutes of events and theses and dissertations portals, signaling what has been done and how such aspects have been produced. Subsequently, the theoretical references that guided the planning and implementation of the training process are presented. The research developed is Participant Research with a qualitative nature, in which the training process was implemented with educators in the area of Natural Sciences who work in the YAE (young and adults education) in a public school in the city of Caçapava do Sul, based on the dynamics of the Three Pedagogical Moments as structuring of critical curricula. The Reality Study allowed the planning to be structured from the following generating question: How to promote the generation of jobs and improvements in public health in the city of Caçapava do Sul? The thematic units discussed in the classes comprise: Health and Pandemic, Tourist hotspots and Geopark and Mining. The analysis took place from the Discursive Textual Analysis through emerging categories to the process. Among the results, we point out the relevance and complementarity that the articulations around the theoretical assumptions Freire- CTS-Andragogy brought to the knowledge and practices of the educator subjects, so that they created paths for the construction of a curricular reorganization for Teaching of Sciences in YAE from a Reality Study. We also present important considerations that permeated the development of this research in the emerging context of a pandemic era, which brought challenges in this path, but which weaves important reflections and contributions to what refers to the Teaching of Science in YAE.